David Smith - Medals for Dishonor (1936-40). Ein ikonografischer Vergleich - Langanke, Cathrin (KIT Scientific Publishing, 2013)
David Smith, who is known in the United States mostly for his abstract sculptures, starts in 1936 with his series Medals for Dishonor (1936-40). By using surrealistic motifs he is showing within this series the horrors of war. Compared with artworks of leading surrealists at that time you can see that there is also a change of iconography: Motifs of violence increase. Could Smiths series of medals therefore be seen as an example for the change of iconography in Surrealism within the 1930s?